2010
DOI: 10.1177/0891988709358589
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity and Specificity of Cognitive Screening Instruments to Detect Cognitive Impairment in Older Adults With Severe Psychiatric Illness

Abstract: Background Older adults with severe psychiatric illness are often treated at community mental health centers (CMHCs) and these individuals commonly have numerous risk factors for cognitive impairment (CI). Brief cognitive screening instruments are frequently used to evaluate cognitive functioning in CMHCs, but the validity of these measures for detecting CI has not been adequately evaluated in this patient population. Objectives To determine the sensitivity and specificity of 2 cognitive screening measures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…Some of these patients might have been misdiagnosed. Because previous studies showed that the MMSE is less sensitive for detecting milder forms of cognitive impairment (43%–43%) [36] than the DemTect (80%–100%) [19], [37], the rate of false-positive diagnoses in our study might have been lower than 24%. However, we were unable to validate the GP diagnoses with our data.…”
Section: Discussionmentioning
confidence: 61%
“…Some of these patients might have been misdiagnosed. Because previous studies showed that the MMSE is less sensitive for detecting milder forms of cognitive impairment (43%–43%) [36] than the DemTect (80%–100%) [19], [37], the rate of false-positive diagnoses in our study might have been lower than 24%. However, we were unable to validate the GP diagnoses with our data.…”
Section: Discussionmentioning
confidence: 61%
“…The Stroop test is a measure of reaction time and investigates executive function and selective attention [Mackin et al, 2010;Seo et al, 2008;Rivera et al, 2015] The MoCA is a cognitive function screening test of various cognitive domains and was included as it has been shown to have 90% sensitivity and 87% specificity that enables identification of 90% of cases with mild cognitive impairment (MCI) and 100% of patients with mild Alzheimer disease. A score of 26/30 and higher on the MoCA is considered normal, and results are corrected with coefficients for different levels of education [Nasreddine et al, 2005].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have included sensitivity and specificity as descriptive measures in their clinical research on cognitive impairment [e.g., [28]]; however, to our knowledge, only Monsch et al [7,8] analysed fluency tasks as diagnostic tests using the ROC approach. These authors make descriptive use of the AUC, sensitivity, specificity, and OCP of both a category fluency task (collapsing the categories animals , fruits , and vegetables ) and a letter fluency task (collapsing F , A , and S ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity is the probability of correct detection of a diseased subject, while specificity is the probability of correct rejection of a healthy control. In less formal words, sensitivity is the power of a test to detect a diseased patient, and specificity is the power to reject a control, non-diseased subject [e.g., [28]]. Thus, every score obtained from our participants in a category fluency task could be considered a provisional cut-off point below which a patient could be diagnosed as diseased and above which a patient could be diagnosed as non-diseased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation